Kurpe O.G., Kukhar V.V. Process development for production of hot rolling coils of steel grade S460MC at wide-strip rolling mill "1700". - Курпе, О. Г.; Кухар, В. В. (Problems of Tribology, 2018)
Process development for production of hot-rolled coils of steel grade S460MC by means of thermomechanical controlled rolling (ТМСР) in accordance with EN 10149-2 at the rolling mill 1700 PJSC “ILYICH IRON AND STEEL WORKS” has been made. The pilot lot of hot-rolled coils of S460MC steel grade with dimensions 2,5 × 1000 мм has been produced and the research of the mechanical properties has been completed. For the first time, the integrated technology for coils thermomechanical rolling of steel grade S460MC in accordance with EN 10149-2 has been developed for rolling at 1700 rolling mill. The controlled air-cooling of coils up to 450 оС after coiling has been implemented in the developed technology. This allows the reduction of air scale layer thickness and improves the surface quality including that for the further processing. The technology has been developed with implementation of the general requirements for the rolled products production by means of thermomechanical controlled rolling by applying the mathematical model of the technological process. The manufacturing possibility of rolled products of steel grade S460MC has been proved utilizing the existing 1700 rolling mill facilities, with no exceeding of the designed capability when utilizing the equipment and without any modernization procedures involved.